Whose song, whose land? Translation and appropriation in Nancy Huston’s Plainsong / Cantique des plaines - Senior, Nancy (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractShort extracts from many songs, particularly hymns and folk or popular songs, are quoted in Nancy Huston's Plainsong / Cantique des plaines. The songs quoted serve as a structuring element of the novel, as a temporal marker, and as a commentary on the action; in addition, some of them are part of the action itself. Their meaning within the novel is sometimes considerably different from the original meaning. In the French version, they carry cultural information but for the most part cannot be sung. As a result, an important element does not survive the passage into French. However, in both versions, the songs make it possible to hear both the voice of the narrator and those of the characters.